2008
DOI: 10.1080/09709274.2008.11906067
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Stress Coping Strategies of Poultry and Cassava Farmers in Nigeria

Abstract: The study focused on stress-coping strategies employed by poultry and cassava farmers based on gender. Very large proportions of them were married (78%) and educated (63.3%). Mean age and mean income of 40 years and N11, 000-N15, 000 respectively were recorded; family size also had a mean of 4 members. With respect to farm size, an average of 5.56 plots was recorded for cassava and 1073 birds were in the poultry farms. Sources of stress are basically financial, weather, work-related, health-related and other p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 3 publications
0
7
0
Order By: Relevance
“…In a study made by Leslie et al (2002) among Mid-Wales farmers it was found that government policy, financial problems and time pressure are the more stress creating factors. Meludu and Bajowa (2008) compared the stress Coping Strategies of Poultry and Cassava Farmers in Nigeria. Financial, weather, work-related, healthrelated and other people, social and psychological stress are the dimensions of stress taken for the study.…”
Section: Introductionmentioning
confidence: 99%
“…In a study made by Leslie et al (2002) among Mid-Wales farmers it was found that government policy, financial problems and time pressure are the more stress creating factors. Meludu and Bajowa (2008) compared the stress Coping Strategies of Poultry and Cassava Farmers in Nigeria. Financial, weather, work-related, healthrelated and other people, social and psychological stress are the dimensions of stress taken for the study.…”
Section: Introductionmentioning
confidence: 99%
“…To them, stress management starts by recognizing the main sources of stress. In the view of Fisher (1994), approaches to managing and coping with stress can be classified into two [15]. The first approach is 'problem-focused coping,' which entails recognizing and distinguishing sources of difficulties for farmers in the hope of providing lasting remedies to these difficulties if possible.…”
Section: Stress Management Among Farmersmentioning
confidence: 99%
“…Regardless of location, it is initially the responsibility of the individual farmer and farmer family to handle mental health and stress, which can be of short or long-term duration. In Nigeria, Meludu and Bajowa (2008) found the influence of farming related problems in social and psychological related stress but found differences between poultry and cassava farmers. Momodu (2002) developed a measure for farm stress.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Despite the availability of human and material resources, the rural populace is still populated with people with low quality of life. Quality life has been identified to be out of reach for the majority of rural dwellers in Nigeria due to lack of access to clean water, health care and good roads, making the rural areas less enjoyable and difficult to live in (Meludu & Bajowa, 2008). Therefore, the rural populace is described as people with poor mental health and closely linked to occupational and environment stress factors (Meludu & Bajowa, 2008).…”
Section: Introductionmentioning
confidence: 99%